Association of the Golgi UDP-Galactose Transporter with UDP-Galactose:Ceramide Galactosyltransferase Allows UDP-Galactose Import in the Endoplasmic Reticulum - Sprong, Hein (The American Society for Cell Biology, 2003)
UDP-galactose reaches the Golgi lumen through the UDP-galactose transporter (UGT) and is used for the galactosylation of proteins and lipids. Ceramides and diglycerides are galactosylated within the endoplasmic reticulum by the UDP-galactose:ceramide galactosyltransferase. It is not known how UDP-galactose is transported from the cytosol into the endoplasmic reticulum. We transfected ceramide galactosyltransferase cDNA into CHOlec8 cells, which have a defective UGT and no endogenous ceramide galactosyltransferase. Cotransfection with the human UGT1 greatly stimulated synthesis of lactosylceramide in the Golgi and of galactosylceramide in the endoplasmic reticulum. UDP-galactose was directly imported into the endoplasmic reticulum because transfection with UGT significantly enhanced synthesis of galactosylceramide in endoplasmic reticulum membranes. Subcellular fractionation and double label immunofluorescence microscopy showed that a sizeable fraction of ectopically expressed UGT and ceramide galactosyltransferase resided in the endoplasmic reticulum of CHOlec8 cells. The same was observed when UGT was expressed in human intestinal cells that have an endogenous ceramide galactosyltransferase. In contrast, in CHOlec8 singly transfected with UGT 1, the transporter localized exclusively to the Golgi complex. UGT and ceramide galactosyltransferase were entirely detergent soluble and form a complex because they could be coimmunoprecipitated. We conclude that the ceramide galactosyltransferase ensures a supply of UDP-galactose in the endoplasmic reticulum lumen by retaining UGT in a molecular complex.